ATRT-18. VALIDATION OF PROTEASOME INHIBITION AS A THERAPEUTIC TARGET IN ATYPICAL TERATOID/RHABDOID TUMORS. Issue 2 (22nd June 2018) - Morin, Andrew; Soane, Caroline; Pierce, Angela; Alimova, Irina; Desmarais, Michele; Zahedi, Shadi; Vibhakar, Rajeev; Griesinger, Andrea; Green, Adam; Hoffman, Lindsey; Levy, Jean Mulcahy
Abstract: Atypical Teratoid/Rhabdoid tumor (AT/RT), characterized by loss-of-function mutations in the SMARCB1 component of the SWI/SNF chromatin-remodeling complex, remains a difficult-to-treat tumor with a five-year overall survival rate of 15–45%. Proteasome inhibition (PI) has recently been opened as an avenue for cancer treatment with the FDA approval of bortezomib (BTZ) in 2003 and carfilzomib (CFZ) in 2012. We performed a drug screen using a panel of 119 FDA-approved drugs in three AT/RT cell lines, and found that both BTZ and CFZ are highly effective in vitro, producing some of the strongest growth-inhibition responses of the entire panel. We further found that these results are consistent through all three established cell lines and a freshly patient-derived tumor culture, and that the effective doses are clinically achievable. BTZ and CFZ are limited for treatment of CNS tumors due to poor blood brain barrier (BBB) penetrance. Marizomib (MRZ) is a newer proteasome inhibitor which has been shown to cross the BBB, and is already in clinical trials for adult high-grade glioma (NCT NCT02330562 and NCT02903069). Proteasome inhibition causes rapid AT/RT cell death in vitro, which may be moderately inhibited by the addition of the ROS scavenger N-acetyl cysteine, consistent with studies in leukemic and glioma contexts. MRZ has been shown to be effective in vivo in other tumor models, and confirmation of the in vivo efficacy of MRZ in an intracranial AT/RT model demonstrating the clinical applicability of PI at both low and high-burden tumor stages is ongoing.